2020
DOI: 10.1007/s12237-020-00844-8
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Interaction Between the Tide and the Storm Surge with the Current due to the River Flow in the Río de la Plata

Abstract: The Río de la Plata estuary (RdP) is characterized by the large flow of its tributary rivers (Q), with an average of 22,000 m 3 s −1 and an interannual variability range from 8000 to 90,000 m 3 s −1 . In this work, the hypothesis that the current due to that flow (CDR) interacts nonlinearly with both the tides and storm surges is evaluated utilizing water level observations and numerical simulations. Two tide gauge time series gathered at the freshwater tidal zone (FTZ) of the RdP are analyzed with the novel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Even though there are several tidal gauges inside the RdP (e.g., Dinápoli et al ., 2020c), Palermo is the only coastal station at the RdP with storm surge and extreme event thresholds and where a large continuous record of observations (from 1905 to the present) is available. It must be taken into account that Palermo is located at the uppermost and narrowest part of the estuary where the storm surge amplitudes (Simionato et al ., 2004) as well as the nonlinear tide–surge interactions (Dinápoli et al ., 2020b) and the nonlinear tide–river and surge–river interactions (Dinápoli et al ., 2020d) maximize. Therefore the station's data provide a good test of the model's ability to integrate the effect of the wind over the whole area of interest in this study (Meccia et al ., 2009).…”
Section: Methodology and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Even though there are several tidal gauges inside the RdP (e.g., Dinápoli et al ., 2020c), Palermo is the only coastal station at the RdP with storm surge and extreme event thresholds and where a large continuous record of observations (from 1905 to the present) is available. It must be taken into account that Palermo is located at the uppermost and narrowest part of the estuary where the storm surge amplitudes (Simionato et al ., 2004) as well as the nonlinear tide–surge interactions (Dinápoli et al ., 2020b) and the nonlinear tide–river and surge–river interactions (Dinápoli et al ., 2020d) maximize. Therefore the station's data provide a good test of the model's ability to integrate the effect of the wind over the whole area of interest in this study (Meccia et al ., 2009).…”
Section: Methodology and Datamentioning
confidence: 99%
“…The water level in the RdP is usually described as the combination of a semidiurnal microtidal regime with diurnal inequalities (D'Onofrio et al ., 2012) and the wind‐driven circulation (Simionato et al ., 2004, 2006a). Large nonlinear interactions occur between the tide, the surge and the river discharge (Etala, 2006a; Dinápoli et al ., 2020b; 2020d). Because of its large length and width, the tide propagates in the RdP as a Kelvin wave, entering the estuary from the south and exiting to the north (Simionato et al ., 2005).…”
Section: Area Of Studymentioning
confidence: 99%
“…The GEBCO 2019 portion of the ACS that we used has been corrected, considering bathymetry measurements provided by the Servicio de Hidrografia Naval. This version is currently the most used for regional numerical models in the region [26,53,54].…”
Section: Bathymetry Datamentioning
confidence: 99%
“…TPXO8 represents tides very well in the region [56]. It has also been used to implement regional models [26,54].…”
Section: Tidal Modelmentioning
confidence: 99%
“…Although TSRIs are rarely studied, they are an important component of storm surges. For example, Dinapoli et al (2021) found that the current due to river flow (CDR) non-linearly interacts with both the tides and storm surges in the Río de la Plata estuary. Their work further suggests the tide-CDR and surge-CDR interactions both induce asymmetries in the water level and the interactions are mainly caused by the quadratic bottom friction.…”
Section: Introductionmentioning
confidence: 99%